Update on Managing Alcoholic Liver Disease and Alcoholic Hepatitis - Summers, Jaye (MD Conference Express, 2015)
Alcoholic liver disease is a leading cause of liver-related mortality and is associated with a significant financial burden. The 2010 treatment guidelines recommend corticosteroids and pentoxifylline, although the evidence for their utility is inconsistent. Although controversial, there is a small group of patients who may be candidates for liver transplant.